Temples of Katas: Their Historical and Religious Significiance - Muhammad Usman Ali (Yakın Doğu Üniversitesi İlahiyat Fakültesi Dergisi)
Temples of Katas (Punjab-Pakistan) hold a very important place in the Hindu mythology especially due to a sacred pond which has different stories regarding its formation. Also this area known as Raj Katas, consists of several historical buildings; mostly related to different branches of Indian religions. Moreover, this place has seen countless invasions and various civilizations, which resulted in impression of other religions on the culture of this area in different periods. However, due to the partition of India their importance has been generally forgotten. This article is aimed at tracing and compiling the history of the temple in order to educate people about its significance. The foremost issue associated with Raj Katas is that no author of international standing has worked on this topic. That resulted in lack of material on this topic.p.p1 {margin: 0.0px 0.0px 0.0px 2.0px; line-height: 8.1px; font: 8.0px 'Times New Roman'; color: #171717}p.p2 {margin: 0.5px 0.0px 0.0px 1.9px; text-align: justify; font: 8.0px 'Times New Roman'; color: #171717}p.p3 {margin: 0.5px 0.0px 0.0px 1.9px; font: 8.0px 'Times New Roman'; color: #171717}span.s1 {letter-spacing: -0.1px}span.s2 {letter-spacing: 0.3px}span.s3 {letter-spacing: 0.6px}span.s4 {letter-spacing: 0.7px}span.s5 {letter-spacing: 1.6px}span.s6 {letter-spacing: 0.9px}span.s7 {letter-spacing: 0.8px}span.s8 {letter-spacing: 1.8px}span.s9 {letter-spacing: 0.2px}span.s10 {letter-spacing: 1.1px}span.s11 {letter-spacing: 1.4px}span.s12 {letter-spacing: 1.5px}span.s13 {letter-spacing: 1.2px}span.s14 {letter-spacing: 0.1px}span.s15 {letter-spacing: -0.4px}span.s16 {letter-spacing: -0.3px}